2002
DOI: 10.1002/rcm.876
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of matrix effects in bioanalytical high‐performance liquid chromatography/tandem mass spectrometric assays: application to drug discovery

Abstract: A series of studies was performed to investigate some of the causes for matrix effects ('ion suppression' or 'ion enhancement') in bioanalytical high-performance liquid chromatography/tandem mass spectrometry (HPLC/MS/MS) assays. Previous studies have reported that matrix effects are mainly due to endogenous components in biological fluids and are a greater concern for electrospray ionization (ESI) than for atmospheric pressure chemical ionization (APCI). In this report we demonstrate that: (1) matrix effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
262
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(266 citation statements)
references
References 16 publications
2
262
0
2
Order By: Relevance
“…Nevertheless, some challenges still remain when performing quantitative LC-MS. An important issue is matrix suppression, a less efficient ionization of the target compound in the presence of other molecules. This phenomenon is well recognized and described in an increasing number of publications [1][2][3][4]. Another complexity in quantitative LC-MS is adduct formation.…”
mentioning
confidence: 91%
“…Nevertheless, some challenges still remain when performing quantitative LC-MS. An important issue is matrix suppression, a less efficient ionization of the target compound in the presence of other molecules. This phenomenon is well recognized and described in an increasing number of publications [1][2][3][4]. Another complexity in quantitative LC-MS is adduct formation.…”
mentioning
confidence: 91%
“…Matrix effect is defined as the effect of co-eluting residual matrix components on the ionization of the target analyte. Typically, suppression or enhancement of analyte response is accompanied by diminished precision and accuracy of subsequent measurements [11][12][13]. Matrix effect thus limits the utility of LC-MS for quantitative analysis.…”
mentioning
confidence: 99%
“…The aim of LC/MS is to separate individual analytes by HPLC such that the eluent delivered to the electrospray ionisation source contains analytes that are resolved from other matrix components. It has been proposed that longer run times and multistep clean up procedures may minimise matrix effects, and also recognised that although improving resolution may reduce matrix effects, problems related to hydrophobic components with retention times which overlap analysis are perhaps most difficult to eliminate [35]. Such effects were observed in this work, the extended run programme using…”
Section: Calibration Based On Standard Additionsmentioning
confidence: 89%
“…Studies on the occurrence of matrix effects in the determination of drugs from biological fluids have also indicated that exogenous materials leached from sample handling during analysis may also play a role in causing matrix effects in LC/MS [35], and consideration should be given to such sources in evaluating methods used for environmental samples.…”
Section: Calibration Based On Standard Additionsmentioning
confidence: 99%